Digital Financial Behavior in a Cashless Society: A Study of Changes in Consumption Patterns - Ummy Kalsum; Hendra Cipta (PT. Hafasy Dwi Nawasena, 2026)
The global transition toward cashless payment systems has significantly transformed consumer financial behavior by changing how individuals perceive, process, and respond to financial transactions. The decreasing physical interaction with money in digital payment systems is believed to reduce the psychological “pain of paying,” thereby encouraging more frequent and impulsive spending behavior. Although the use of digital payment platforms continues to increase rapidly, particularly in emerging digital economies, the relationship between cashless payment adoption, digital financial behavior, and changes in consumption patterns remains insufficiently explored. This study therefore aims to examine the influence of cashless payment adoption, digital financial behavior, and financial self-control on consumption pattern changes among active digital payment users in Indonesia. Using a quantitative survey design, data were collected from 125 respondents who actively use digital payment platforms and analyzed through multiple linear regression analysis supported by classical assumption testing to ensure model validity. The findings reveal that cashless payment adoption (β = 0.389, p < 0.001) and digital financial behavior (β = 0.304, p = 0.005) significantly increase consumptive behavior, while financial self-control shows a significant negative effect (β = −0.241, p = 0.024), indicating its role in limiting excessive consumption tendencies. Furthermore, the model explains 59.3% of the variance in consumption pattern changes (R² = 0.593), suggesting that these variables substantially contribute to evolving spending behavior in the digital era. Overall, the study concludes that cashless payment systems accelerate shifts toward more frequent and less deliberate spending patterns, while financial self-control functions as an important counterbalancing mechanism, highlighting the need for behaviorally informed digital financial literacy programs and spending-awareness features within digital payment applications.